Measurements of the thermal conductivity of reference liquids using a modified transient hot-wire needle probe. (15th June 2022) - Merritt, B.; Seneca, M.; Larson, S.; Davis, K.; Munro, T.
Highlights: A modified transient hot-wire needle probe is investigated as a technique for measuring thermophysical properties of a variety of liquids. Seven liquids are selected for study, whose thermal conductivities, corrosive potential, and electrical conductivities vary substantially. Temperature-dependent correlations are developed for all measurements with uncertainty being quantified. Abstract: Many power generation processes feature some type of working fluid that plays a critical role in the transfer of heat throughout the system. To optimize thermal efficiencies, an accurate characterization of the temperature-dependent thermal conductivity of the fluid is needed. This study develops a time-domain Modified Transient Hot-wire Needle Probe to overcome phenomena that have impaired traditional measurement techniques when the fluid is both corrosive and at an elevated temperature. First, the physical design of the instrument is presented to demonstrate features that limit interference from corrosion, electrical conduction, and convective and radiative heat transfer. Next, a governing equation for 1D (radial) heat conduction is fully developed using the thermal quadrupoles technique. A finite-element study is performed for validation. A sensitivity analysis is done to assess the time-dependent influence of critical parameters in the governing equation for several samples. Finally, thermal conductivity measurements are presented for seven different liquid substances by fitting the thermal model to experimental data across a range of temperatures. Reference correlations are included for comparison. The sample thermal conductivity and ambient temperature of the experimental conditions range from 0.125–16.5 W m K and 10–400 ∘ C, respectively. The total uncertainty, comprised of both the experimental design and fitting process, of all measurements is quantified.